PENERAPAN SISTEM INFORMASI PEMESANAN BERBASIS WEB PADA CV SELEKSI ALAM MURIA - Niken Ayu Ambarwati; Anteng Widodo (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This community service activity aims to implement a web-based ordering information system at CV Seleksi Alam Muria to address problems related to manual ordering and data management. Manual ordering processes resulted in unstructured transaction records, difficulties in sales recapitulation, and delays in customer service. The implementation methods included partner needs analysis through observation and interviews, system design using use case diagrams, development of a web-based ordering information system, as well as system testing and user assistance. The results show that the implemented system successfully integrates ordering processes, product management, payment validation, and sales reporting into a centralized system. The system improves operational efficiency, accelerates service processes, and increases data recording accuracy. In addition, the system serves as a digital promotion medium that expands the partner’s market reach. Therefore, the implementation of a web-based ordering information system can support MSME digital transformation and enhance service quality and business competitiveness.